Pengaruh Keanggotaan Komite Audit Dan Keahlian Keuangan Komite Audit Terhadap Pengungkapan Kelemahan Pengendalian Internal Dan Implikasinya Terhadap Efektivitas Test Substantif Transaksi - Devi Kania Dewi (Jurnal Riset Mahasiswa, 2020)
This study aims to determine the influence of the audit committee membership and the audit committee's financial expertise on the disclosure of internal control weaknesses and their implications for the effectiveness of the substantive test transactions at PT Dirgantara Indonesia (Persero). The method used was a survey, descriptive and verification approaches and primary data. Based on the research results, it is known that the audit committee membership has an effect of 21.1% and the financial expertise of the audit committee is 22.8% on the disclosure of control weaknesses. Simultaneously it gives an effect of 43.8%. Disclosure of internal control weaknesses has an effect of 20.6% and the effect of audit committee membership on the effectiveness of the substantive testtransactions of 11.2%. The audit committee's financial expertise exerted 14.6% effect on the effectiveness of the substantive test of the transaction. Audit committee membership and audit committee financial expertise simultaneously affect the effectiveness of the substantive test transactions by 25.8%.